Nanostores and Society 5.0: Paradigm Shifts in Supply Chains through Bibliometric Analysis - ORTEGA-JIMENEZ, CESAR HUMBERTO; MOHMMAD ALHUSBAN, ABDALLAH OMAR (LACCEI, 2024)
This groundbreaking study employs bibliometric analysis to unravel the dynamic landscape of supply chains amid the emergence of Society 5.0. Focusing on a captivating anomaly, our investigation reveals a conspicuous dearth of research dedicated to "nanostores" within this evolving paradigm. This compelling revelation, extracted from an extensive review of scholarly works across 10 countries, not only highlights the escalating significance of Society 5.0 but also identifies critical gaps in knowledge awaiting exploration. As we stand on the brink of profound technological advancements and societal metamorphosis, this study accentuates the pressing need for an in-depth exploration of the intricate link between nanostores and Society 5.0. Serving as a clarion call, our research sparks discourse and urges further investigation to unlock the latent potential and profound implications of nanostores within this paradigm shift. Join us on a journey into the future of supply chains, where nanostores emerge as pivotal players, potentially holding the key to navigating the uncharted territory of Society 5.0. Brace yourself for an enthralling exploration as we delve into the uncharted realm of possibilities that nanostores present within this transformative paradigm.